Developing Civic Education Learning through Cosmopolitan Value Perspective - Halimah, Lili (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
This study aims to provide insight to PPKn teachers because it is part of the research on citizenship development studied through the perspective of cosmopolitan values. In this era of globalisation, the Indonesian people are faced with global forces that go hand in hand with cosmopolitanism. The main problem is how much Civic Education (Civics Education) is influenced by cosmopolitan values? The research locations are spread in Cimahi Tengah, Utara, and Selatan totaling 45 schools. The study population totaled 20,702 with a sample of 400 students. The study used the Cross-Sectional Survey method. Retrieval of data through a questionnaire. Data analysts were carried out with Structural Equation Modeling competency tests. The results showed that the impact of cosmopolitan values ​​on Civics learning was significant (with R2 = 0.6971 or 69.71%), indicating the process of harmonizing cosmopolitan values ​​in secondary school students in civics learning. Cosmopolitan values ​​have a higher effect (31.44%) than Civics learning, which shows that the cosmopolitan values ​​studied in Civics affect middle school students in Cimahi even though only 13.42%. Cosmopolitan values ​​are an important factor in developing Civics learning amid the swift currents of globalisation. This has implications for the government to review the Civics curriculum by paying attention to the phenomena that exist in society, namely the strengthening of globalisation and cosmopolitan values ​​that are increasingly widespread in all aspects so that it is feared to have an impact on student behavior into global culture so that there is a shift in the mindset and lifestyle of students in Cimahi City. Thus, through this research, at least PPKn teachers or relevant researchers can minimize the phenomena and the negative impacts arising from globalisation. Keywords: learning, civic education, and cosmopolitan values ABSTRAK Penelitian ini bertujuan untuk memberikan wawasan kepada para guru PPKn karena merupakan bagian dari penelitian pengembangan kewarganegaraan dikaji melalui perspektif nilai kosmopolitan. Di era globalisasi ini, masyarakat Indonesia dihadapkan pada kekuatan globalisasi yang beriringan dengan kosmopolitan. Masalah utama yaitu seberapa besar pembelajaran Pendidikan Kewarganegaraan (PKn) dipengaruhi oleh nilai kosmopolitan? Lokasi penelitian tersebar di Cimahi Tengah, Utara, dan Selatan berjumlah 45 sekolah. Populasi penelitian berjumlah 20.702 dengan sampel 400 siswa. Penelitian menggunakan metode Cross-Sectional Survey. Pengambilan data melalui kuesioner. Analis data dilakukan dengan uji kompetensi Structural Equation Modeling. Hasil penelitian menunjukan bahwa dampak nilai kosmopolitan terhadap pembelajaran PKn sudah signifikan (dengan R2 = 0,6971 atau 69,71%), menunjukkan adanya proses harmonisasi nilai kosmopolitan pada siswa sekolah menengah dalam pembelajaran civics. Nilai kosmopolitan memiliki pengaruh yang lebih tinggi (31,44%) dari pembelajaran PKn, yakni menunjukkan bahwa nilai kosmopolitan yang dipelajari dalam PKn berpengaruh pada siswa sekolah menengah di Cimahi walaupun hanya 13,42%. Nilai kosmopolitan menjadi faktor penting dalam mengembangkan pembelajaran PKn ditengah derasnya arus globalisasi. Hal ini berimplikasi bagi pemerintah untuk mengkaji kembali kurikulum PKn dengan memperhatikan fenomena yang ada di masyarakat yakni menguatnya globalisasi dan nilai kosmopolitan yang semakin meluas ke seluruh aspek sehingga dikhawatirkan berdampak bagi perilaku siswa ke dalam budaya global sehingga terjadi pergeseran pada pola pikir, dan gaya hidup siswa di Kota Cimahi. Dengan demikian melalui penelitian ini setidaknya para guru PPKn atau peneliti yang relevan dapat meminimalisir fenomena dan dampak negatif yang ditimbulkan dari globalisasi. Kata kunci: pembelajaran, pendidikan kewarganegaraan, nilai kosmopolitan